Performance in attention tasks of schoolchildren in primary education with and without oral breathing (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2025)
Breathing influences craniofacial and systemic development. When it's through the mouth, it can affect cognitive performance during the school years. This study compared sustained attention performance in schoolchildren with and without mouth breathing during the second semester of 2023 in Temuco. The methodology involved an observational, cross-sectional, and comparative scope design, with non-probabilistic convenience sampling, excluding known respiratory or cognitive pathologies. 45 students between 7 and 9 years old participated. A speech therapy protocol and the D2-R test were used to evaluate breathing and attention, respectively. 17 participants had mouth breathing (38%). No significant differences were found in the D2-R test when grouped by performance (chi-square, p = 0.059). When comparing scores, there was significance overall and in the male group (t-test, p = 0.040 and p = 0.035, respectively). The results suggest potential attentional difficulties in schoolchildren with mouth breathing.
Keywords: oral breathing; attention; education; cognitive skills